104 Assessing for Delirium in A District General Emergency Department—Why are We Failing and How can We Improve?. (16th March 2021) - Pickard, J; Morris, R; Crawford, I; Mansi, R
Abstract: Introduction: Delirium is among the most common of medical emergencies with a prevalence of 20% in adult acute general medical patients. Despite this delirium is underdiagnosed and treatment is variable. Assessment of delirium is missed or carried out unreliably in EDs. Methodology: Using the Model for Improvement, we developed a driver diagram to plan our project. Assessing whether patients over 65 years old were assessed for delirium during their visit to the ED using a validated tool over a 6-month period. Evaluating the impact of our interventions using annotated run charts. Exclusion criteria—GCS under 13, NEWS2 greater than 5. Aim: Identify current performance of delirium assessment in over 65 s in Weston General Hospital ED and improve to 100% of over 65 s screened. Assess whether this has been communicated in the discharge summary. Results: Baseline data showed 22.2% (4/18) of patients meeting inclusion criteria were screened for delirium. We implemented multiple interventions over a 2-month period—discussing at ED handover, hospital wide email, presentation at grand round and displaying a poster in the ED. In the 6 weeks after the interventions were implemented there was increase to 45.4% (15/33) of patients over 65 screened. Delirium/cognitive impairment identified in 42.5% (48/113) of patients screened. This is higher than the national average of hospital admissions therefore it is likely people screen those who display signs of delirium. Cognitive impairment communicated in discharge letter in only 29.4% (33/113) of all patients. Conclusion: There has been a great improvement in delirium screening. However, we did not meet our target of 100% of patients being screened. Interventions currently being implemented—addition of SQID tool to minors clerking document, addition of compulsory tick box delirium question on all discharge summaries. Further data will be collected to assess effectiveness of these interventions.